The potential threat of multisystem inflammatory syndrome in children during the COVID‐19 pandemic. Issue 1 (13th October 2020) - Rothan, Hussin A.; Byrareddy, Siddappa N.
Abstract: Multisystem inflammatory syndrome in children (MIS‐C) during the COVID‐19 pandemic raised a global alert from the Centers for Disease Control and Prevention's Health Alert Network. The main manifestations of MIS‐C (also known as pediatric MIS (PMIS)) in the setting of a severe inflammatory state include fever, diarrhea, shock, and variable presence of rash, conjunctivitis, extremity edema, and mucous membrane changes. In some cases, these symptoms progressed to multi‐organ failure. The low percentage of children with asymptomatic cases compared with mild illness and moderate illness could be correlated with the rare cases of MIS‐C. One potential explanation for the progression to severe MIS‐C disease despite the presence of readily detectable anti‐SARS‐CoV‐2 antibodies could be due to the potential role of antibody‐dependent enhancement (ADE). We reason that the incidence of the ADE phenomenon whereby the pathogen‐specific antibodies can promote pathology should be considered in vaccine development against SARS‐CoV‐2.